Women's Perception Regarding Respectful Maternity Care during Child Birth at a Facility-Based Hospital in Koshi Province (Purbanchal University Health Journal, 2024)
Introduction: Respectful Maternity Care (RMC) is the universal right of childbearing women. It encompasses kind and dignified treatment and preferences to preserve their right to have a companion or perform cultural rituals. RMC has been promoted due to the importance of ethical, psychological, social, and cultural aspects of childbirth among different populations.Objective: The study aimed was to assess the women's perceptions of respectful maternity care during childbirth at a selected facility-based hospital in Koshi Province.Method: A descriptive cross-sectional study was conducted among 220 postnatal mothers who had a normal vaginal delivery and were admitted to the Postnatal ward of Koshi Hospital. The convenience sampling method was used to select the sample. Data were collected by face-to-face interview technique with a standard Respectful Maternity Care (RMC) Scale, which consists of four dimensions of RMC, such as friendly, abuse-free, timely, and discrimination-free care. Descriptive and inferential statistics (the chi-square test) were used to analyze the data.Result: A total of 127 (57.7%) respondents stated that they had experienced overall dimensions of RMC, with a mean score and ± SD (58.86 ± 4.909). Among the four dimensions of RMC, More than half (59.5%) of respondents received timely care likewise 54.5% of respondents experienced friendly care, 51.8% of respondents received abuse-free care and 50.9% of respondents experienced discrimination-free care. The perception of overall dimensions of RMC was found to be significantly associated with education, type of family, family income per month and number of antenatal visits.Conclusion: The study concluded that more than half of the respondents experienced overall dimensions of Respectful Maternity Care and among the four dimensions, the perception score was highest in timely care and lowest in discrimination-free care.